Case Report: IVC-agenesis and FVL mutation; successful DVT/PE treatment with direct oral anticoagulation (factor Xa inhibitor) - Siddiqui, Abid; Hatfield, Tara; Nguyen, Quynh; Waris, Waris (Frontiers in Cardiovascular Medicine, 2025)
Inferior vena cava (IVC) agenesis is a rare congenital anomaly that has been implicated in up to 5% of unprovoked deep vein thrombosis (DVT) cases in young men under 30 years old. We present the case of a 28-year-old obese Caucasian male who arrived at our hospital with significant pain and swelling in his right lower extremity. The patient had no prior medical history or family history of DVT or cardiovascular conditions. A venous Doppler ultrasound revealed an extensive right lower extremity DVT. Further imaging with a computed tomography (CT) pulmonary embolism (PE) protocol scan of the chest and abdomen identified IVC agenesis along with pulmonary emboli in the left central pulmonary arteries. A hypercoagulability workup was positive for a heterozygous Factor V Leiden (FVL) mutation, an additional thrombophilic risk factor. The patient was initially managed with an intravenous heparin drip and was later transitioned to long-term direct Factor Xa inhibitor therapy. To our knowledge, this is the first reported case of extensive venous thromboembolism (VTE) due to concurrent IVC agenesis and FVL mutation successfully treated with direct Factor Xa inhibition. This case highlights the complexity of managing patients with multiple thrombogenic risk factors and raises a discussion on the rationale for lifelong anticoagulation in such individuals.